ANALISIS PENGARUH PRODUCT ATTRIBUTE DAN LUXURY VALUE TERHADAP LOYALITAS PENGGUNA IPHONE DENGAN KEPUASAN SEBAGAI VARIABEL INTERVENING - Ivan Eduardo Puntoh (Program Studi Ilmu Administrasi Bisnis, FIABIKOM, Unika Atma Jaya, 2018)
This research is purposed to analyze whether product attribute and luxury value directlyaffecting iPhone’s customer’s loyalty or indirectly through customer’s satisfaction first, thento customer’s loyalty. The method used for this research is quantitative analysis, withsnowball sampling technique to collect 200 samples from Atma Jaya University’s studentsthat using iPhone. Path analysis is used in this research both as framework and analysistechnique, to determine the direct and indirect values. The result showed that the direct pathhas higher value than the indirect path.